Breaking the Frames : Anthropological Conundrums - Stewart, Pamela J.; Strathern, Andrew J. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book argues that the breaking and re-making of frames of analysis underlie the history of theorizing in anthropology. Pamela J. Stewart and Andrew J. Strathern note that this mode of analysis risks fabricating over-essentialized dichotomies between viewpoints. The authors advocate a mindful, nuanced, people-centered approach to all theorizing-one that avoids total system approaches (-isms) and suggest that theory should relate cogently to ethnography. Mindful anthropology, as this book envisages it, is not a specific theory but a philosophical aspiration for the discipline as a whole. Pamela J. Stewart (Strathern) and Andrew J. Strathern are well-known international lecturers, having lived and worked globally. They have published over 50 books, as well as hundreds of articles, book chapters, and essays on their research in Asia, Europe, and Oceania. They are also the series editors for Palgrave Studies in Disaster Anthropology. v>.
Keywords: Social sciences.; Ethnology.; Social sciences -- Philosophy.; elektronické knihy; electronic books